Risk of divorce and likelihood of having additional children among families with children with spina bifida : A Swedish population-based longitudinal register study - Mtutu, R. Samu ; 0000-0002-0140-1928; Alriksson-Schmidt, Ann I.; Müller, Vibeke; Jarl, Johan ; 0000-0002-9274-2479 (Research in Developmental Disabilities, 2025)
Background: To raise a child with disability might present challenges and affect the functioning of the family unit. In this study, the risk of divorce for parents of children with spina bifida and the probability of having additional children were analysed. Methods: Longitudinal, matched case-control, data between 2004 and 2014 from multiple linked Swedish Population Registers were analysed using Cox proportional hazard models with interval censoring. Results: The results showed a reduced risk of divorce among parents of children with spina bifida compared to parents of children who did not have spina bifida. Some indications of heterogeneous effects were noted; a stronger protective association was noted among parents who are married compared to cohabiting, have higher education, and where the mother is older at the birth of the child with spina bifida (34 + years). No association was found on having additional children after the birth of a child with spina bifida. Conclusion: The results should be understood in the Swedish context, which is known for its comprehensive welfare system. Future research should investigate the mechanisms behind these results. What this paper adds?: This study contributes to the field by utilizing population-based register data, which is rare for spina bifida research. Comparison to prior studies indicates that there is substantial heterogeneity across disabilities indicating that while some research can be conducted at the broad disability level, in certain contexts it might be inappropriate to study disability as a group or generalising the results from one disability to the next.
Publisher Copyright: © 2025 The Authors
Keywords: Divorce; Early-onset disability; Family formation; Spina bifida; Sweden